2022
DOI: 10.1177/23259671221114353
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of ACL Injury for Female but Not Male Soccer Players on Artificial Turf Versus Natural Grass: A Systematic Review and Meta-Analysis

Abstract: Background: Both natural grass (NG) and artificial turf (AT) are popular playing surfaces for soccer. Biomechanical studies have found increased frictional forces on AT that may lead to anterior cruciate ligament (ACL) injury. The increased risk of ACL injury during soccer in female participants may amplify this effect. Purpose: To systematically review the literature for studies comparing ACL injury risk in soccer players on AT versus NG and to specifically determine whether there were differences in injury r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…The rapid growth of women's football (soccer) participation is bringing about increasing rates and earlier occurrence of primary Anterior Cruciate Ligament (ACL) injury. 1,2 Several authors have demonstrated that female footballers are at overall higher risk of ACL injury than their male counterparts 1,3,4 and are less responsive to targeted preventative interventions e.g., the FIFA 11+ program. 1,5,6 Therefore, a deeper comprehension of modifiable risk factors, such as ACL injury biomechanics, has been advocated to mitigate the injury risk in female football academies.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid growth of women's football (soccer) participation is bringing about increasing rates and earlier occurrence of primary Anterior Cruciate Ligament (ACL) injury. 1,2 Several authors have demonstrated that female footballers are at overall higher risk of ACL injury than their male counterparts 1,3,4 and are less responsive to targeted preventative interventions e.g., the FIFA 11+ program. 1,5,6 Therefore, a deeper comprehension of modifiable risk factors, such as ACL injury biomechanics, has been advocated to mitigate the injury risk in female football academies.…”
Section: Introductionmentioning
confidence: 99%
“…While the first field of study is examining the toxic substances contained in artificial turf fields, (1,2,(4)(5)(6)(7)(8)(9) the other field of study is examining the effects of artificial turf fields on sports injuries. (10)(11)(12)(13)(14)(15)(16) In a study on metals that included mercury (Hg), arsenic (As), lead (Pb), zinc (Zn), aluminum (Al), iron (Fe), and magnesium (Mg) in samples taken from 32 different synthetic fields, a total of 25 metals were examined and it has been reported that Mg, Fe and Zn levels were significantly higher than those of the other metals. (8) In addition, in studies on crumb rubber, it has been reported that while tire rubber contains high levels of Zn, it also contains Fe and Mg, albeit at low levels.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing diffusion of sports disciplines very similar to football (futsal and beach soccer in the first instance) and the spread of playing surfaces of different nature (artificial vs. natural, artificial of different and latest generation) have highlighted the need to investigate the role that these play in the realisation of the performance (Gould et al, 2023;López-Fernández et al, 2018;Williams et al, 2011), load and skills associated with the sport (Strutzenberger et al, 2022;Kuitunen et al, 2023;Xiao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%